Osteosarcoma patient with Li-Fraumeni syndrome: the first case report in Vietnam - Le, Thanh Thien; Ha, Tung Sy; To, Linh Mai; Dang, Quang Minh; Bui, Hoa Thi Phuong; Tran, Thanh Duc; Vu, Phuong Thi; Giang, Hoan Bao; Tran, Dung Trung; Nguyen, Xuan-Hung (Frontiers in Oncology, 2024)
Li–Fraumeni syndrome (LFS) is a hereditary disorder characterized by an increased risk of developing multiple early-onset cancers, primarily due to germline TP53 mutations. Women and men with this mutation face lifetime cancer risks of 90% and 70%, respectively. This report describes the first documented case of LFS with clinical information in Vietnam involving a 9-year-old child diagnosed with osteosarcoma who had multiple first- and second-degree relatives with cancer. Whole-genome sequencing (WGS) revealed a heterozygous, pathogenic, autosomal dominant TP53 variant NM_000546.6:c.733G>A (p.Gly245Ser) and a translocation in the 3’UTR of the ATMIN gene with unknown pathogenicity in both the patient and her mother. Sanger sequencing confirmed the presence of the TP53 c.733G>A mutation, which was subsequently detected in extended family members. Of the 17 family members invited for testing, only 8, none of whom currently have cancer, agreed to participate: all tested negative for the mutation. This case highlights the importance of genetic testing for the early detection and management of cancers in LFS patients. It also underscores significant barriers to genetic screening in Vietnam, including limited access and the psychosocial consequences of testing, which emphasize the need for improved genetic counseling and surveillance strategies that are tailored to local contexts.